Long Lasting Chronic Resistive Training Effects on Circulating S-Klotho and IGF-1 - Saghiv, Moran; Sherve, Chris; Goldhammer, Ehud; Ben-Sira, David; Sagiv, Michael (Archives of Clinical and Biomedical Research, 2017)
Purpose: The purpose of the present study was to examine the effects of long lasting chronic resistive training on circulating s-klotho s and IGF-1 levels in young adult. Methods: 50 national level powerlifters and 50 age matched untrained young adults (27.1±1.0 and 26.5±1.0 years respectively). Following overnight fasting forearm vein blood samples were taken, circulating s- Klotho were examined by means of a-klotho Enzyme Linked Immunosorbent Assay ELISA kit. A chemiluminescent immunometric method was applied in order to define serum IGF-1 levels. Results: No significant differences were seen between the weightlifters and untrained young adults for s-Klotho (421.0±76.0 and 435.2 ±89.0 pg·mL-1 respectively). However, IGF-1 levels were significantly (p<0.05) higher in the weightlifters compared to the untrained subjects (110.6±16.4 and 77.6±23.2 mmol·L-1 respectively). Conclusions: It seems that long lasting resistive training did not influence circulating levels of s-Klotho, while the increased circulating IGF-I may, at least in part, mediate increases in strength, power and muscle hypertrophy.